2024
DOI: 10.3390/rs16060988
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Machine Learning Ensembles for Landslide Susceptibility Mapping in Northern Pakistan

Nafees Ali,
Jian Chen,
Xiaodong Fu
et al.

Abstract: Natural disasters, notably landslides, pose significant threats to communities and infrastructure. Landslide susceptibility mapping (LSM) has been globally deemed as an effective tool to mitigate such threats. In this regard, this study considers the northern region of Pakistan, which is primarily susceptible to landslides amid rugged topography, frequent seismic events, and seasonal rainfall, to carry out LSM. To achieve this goal, this study pioneered the fusion of baseline models (logistic regression (LR), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 119 publications
0
1
0
Order By: Relevance
“…In particular, Random Forest (Breiman 2001), is a powerful ensemble algorithm that is well-suited for enhancing generalizability, and XGBoost (Chen and Guestrin 2016) is another ensemble algorithm that is known for improving prediction accuracy on lesser understood data at scale. While this study is a new application of these learning methods in the field of glacial geomorphology, Random Forest and XGBoost algorithms have been recently employed for other automated mapping applications in geology (e.g., Zhao and Chen 2023, Li et al 2022, Ali et al 2024 where they have both demonstrated high predictive performance.…”
mentioning
confidence: 99%
“…In particular, Random Forest (Breiman 2001), is a powerful ensemble algorithm that is well-suited for enhancing generalizability, and XGBoost (Chen and Guestrin 2016) is another ensemble algorithm that is known for improving prediction accuracy on lesser understood data at scale. While this study is a new application of these learning methods in the field of glacial geomorphology, Random Forest and XGBoost algorithms have been recently employed for other automated mapping applications in geology (e.g., Zhao and Chen 2023, Li et al 2022, Ali et al 2024 where they have both demonstrated high predictive performance.…”
mentioning
confidence: 99%